Minority Labeling of "Desi" And "Muslim" As Seen in Samira Ahmed's Internment - Prasetya, Asfarina; Ubaidillah, Ubaidillah (Sunan Kalijaga: International Journal of Islamic Civilization, 2024)
This article aims to expose the labeling of “Desi” and “Muslims” as minority groups in a country where the majority of the population is from external groups. In the novel entitled Internment, it is found that the appearance of labels in the Internment affects the position of all characters. This study focuses on the causes that influence the emergence of the labels "Desi" and "Muslim" and how these labels are used for all characters in the novel Internment by Samira Ahmed. The data were collected through the documentation method or the observation method. The theory of language and Identity by Joanna Thornborrow is used as the main theory, while the theory of situation context by Bronislaw Malinowski is used as a supporting theory. These two theories are used to identify the types of labels and analyze the causes of labels appearing in the novel. This analysis indicates that negative labeling on utterances containing the labels "Desi" and "Muslim" becomes the most dominant label and often appears in every utterance. Also, utterances containing negative labels come from the internal group. It shows that sometimes the group is not confident in their identity when they are in a minority group in a country where the majority of the population comes from an external group.